2021
DOI: 10.3390/ijerph182010800
|View full text |Cite
|
Sign up to set email alerts
|

Trait Emotional Intelligence and Happiness of Young Adults: The Mediating Role of Perfectionism

Abstract: Perfectionism or a tendency to aim for an unrealistic standard can impair happiness. However, the potential mechanisms of perfectionism to explain the association between trait emotional intelligence (EI) and happiness are still understudied. This study explores the mediating role of perfectionism in the relationship between trait emotional intelligence (EI) and happiness among young adults. A cross-sectional sample of 259 young adults aged between 18 to 35 years old was recruited. All analyses were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Moreover, studies may focus not only on the effects of EI facets in happiness but in other potential mediating and moderating factors in in this relationship. 47 Accordingly, future works in this line may follow the current results to test the cascading model of EI, with the aim of confirming whether self-focused emotion appraisal may lead to increased teachers' happiness through self-focused emotion regulation and reduced stress. 40 Second, despite the results being based on a relatively large sample of teaching professionals, the incidental sampling method used with a sample of Spanish teachers makes it difficult to generalize the current findings.…”
Section: Limitations and Future Researchmentioning
confidence: 74%
“…Moreover, studies may focus not only on the effects of EI facets in happiness but in other potential mediating and moderating factors in in this relationship. 47 Accordingly, future works in this line may follow the current results to test the cascading model of EI, with the aim of confirming whether self-focused emotion appraisal may lead to increased teachers' happiness through self-focused emotion regulation and reduced stress. 40 Second, despite the results being based on a relatively large sample of teaching professionals, the incidental sampling method used with a sample of Spanish teachers makes it difficult to generalize the current findings.…”
Section: Limitations and Future Researchmentioning
confidence: 74%
“…The fact that the high perfectionism group obtained significantly higher scores than the other profiles in emotional attention, and that this was explained by the high levels of both PS and PC, is still a surprising result considering that the previous literature has provided preliminary evidence about the negative association between PC and EI [ 22 26 , 29 ]. However, it must be remembered that none of these previous studies have been based on the TMMS scale.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, results also showed that EI fully mediated the link between PS and satisfaction with life and partially mediated the link between PC and depression, stress and satisfaction with life. More recently, Wilson et al [ 25 ] and Badri et al [ 26 ] using, respectively, a sample of 277 Canadian undergraduates ( M age = 18.01, SD = 1.46) and 259 English young adults, found that both PS and PC significantly and negatively correlated with EI. In contrast, with a sample of 120 middle school children from Slovenia, Doktorová, and Varecková [ 27 ] observed nonsignificant associations between PS, PC, and EI, except for concern about making mistakes, which was the only indicator of PC negatively and significantly associated with EI.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, trait EI seems pertinent in enhancing individuals' quality of life across the different aspects of health and well-being and personal and professional adjustment. [11][12][13][14] For example, trait EI has revealed a steady relationship with happiness in young adults, 15 leadership behavior and skills, 16 work engagement, 17 job satisfaction and flourishing, 18 and maintaining positive relations among coworkers. 19 Trait EI has also been found to be a good predictor of positive mental health, 12 lower cortisol secretion levels in stressful conditions, 20 and helps to deal with stressful situations.…”
Section: Introductionmentioning
confidence: 99%